2003
DOI: 10.1124/mol.63.3.732
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity Reactions to Carbamazepine: Characterization of the Specificity, Phenotype, and Cytokine Profile of Drug-Specific T Cell Clones

Abstract: Administration of carbamazepine (CBZ) causes hypersensitivity reactions clinically characterized by skin involvement, eosinophilia, and systemic symptoms. These reactions have an immune etiology; however, the role of T cells is not well defined. The aim of this study was to characterize the specificity, phenotype, and cytokine profile of CBZ-specific T cells derived from hypersensitive individuals. Proliferation of blood lymphocytes was measured using the lymphocyte transformation test. CBZ-specific T cell clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
173
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(188 citation statements)
references
References 36 publications
14
173
0
Order By: Relevance
“…Evidence to support these hypotheses is gained by the detection of drug-specifi c antibodies and T cells in some patients with DILI. [15][16][17][18][19][20][21] This review will focus on the involvement of the innate and adaptive immune systems in the pathogenesis of DILI.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence to support these hypotheses is gained by the detection of drug-specifi c antibodies and T cells in some patients with DILI. [15][16][17][18][19][20][21] This review will focus on the involvement of the innate and adaptive immune systems in the pathogenesis of DILI.…”
Section: Introductionmentioning
confidence: 99%
“…In this alternate hypothesis, there is a direct, non-convalent binding of the drug to the T cell receptor to specific T cell clones. Drug-specific T cells have been identified for lamotrigine and carbamazepine (25,26). Handoko and coworkers have also confirmed that the association for T cellmediated reactions was strongest in cutaneous reactions (13).…”
Section: Discussionmentioning
confidence: 57%
“…Naisbitt et al observed in patients with CBZinduced AHS a clonal proliferation of CD4+ or CD4+/CD8+ cells, associated to the interferon-y secretion and to cytotoxic effects (27).…”
Section: Pathogenesismentioning
confidence: 99%
“…The variability in the clinical presentation ofAHS, such as epidermal eruptions and mucosal blistering in SJS, epidermal necrosis and delamination in TEN, or eosinophilia in DRESS, is likely to reflect host-specific metabolic and immunologic reactions associated with T-cell-mediated responses in these tissues (27)(28)(30)(31). These reactions include varying levels of cytochrome induction: MHC/non-MHC-dependent T-cell activation; involvement of cytotoxic CD8+ and CD4+ mediated responses; expression of adhesion and homing molecules on keratinocytes; chemokine release with infiltration by monocytes/macrophages and eosinophils.…”
Section: Pathogenesismentioning
confidence: 99%